Advances in enterprise engineering IX : 5th Enterprise Engineering Working Conference, EEWC 2015, Prague, Czech Republic, June 15-19, 2015, Proceedings /: 5th Enterprise Engineering Working Conference, EEWC 2015, Prague, Czech Republic, June 15-19, 2015, Proceedings. (2015) - Unknown
No abstract available